Penerapan Sistem Penjualan Makanan Berbasis Android Kotlin Dengan Metode Prototype - Wahyu Santoso; Fajar Agung Nugroho (CV. Multi Kreasi Media, 2024)
Citra Cafe's cafeteria is a business focused on food sales. Currently, the food ordering process is done with customers coming to the canteen cashier. However, this ordering method often encounters problems when there are many customers who want to order food, such as mixed-up orders due to the lack of order recording. The objective of this research is to create an Android-based food sales system that can transform the previously manual sales system into a computerized one. The food sales application at Citra Cafe's cafeteria is a system that provides convenience in ordering food and reduces errors such as mixed-up orders. For this research, a qualitative approach is implemented using the prototype method for system development. To gather data, this study utilizes interview techniques and observations to obtain processable data that can be used to design the system according to the requirements. Furthermore, this research also applies blackbox and whitebox testing methods to test the designed system. With the implementation of this food sales system, it will ease the cafeteria attendants' work in managing customer orders, eliminating mixed-up orders, and facilitating customers in ordering food as they no longer need to queue in front of the cashier to place their orders.